Arthroscopic Soft Tissue Stabilization for Traumatic Anterior Shoulder Instability in Elite Collision Athletes: Is it Sufficient?. Issue 7 (29th July 2019) - Shota, Hoshika; Sugaya, Hiroyuki; Takahashi, Norimasa; Matsuki, Keisuke; Tokai, Morihito; Morioka, Takeshi; Ueda, Yusuke; Hamada, Hiroshige; Takeuchi, Yasutaka
Objectives: Surgical options for shoulder instability in collision athletes remain controversial. Although arthroscopic soft tissue stabilization is widely accepted treatment for shoulder instability, many surgeons prefer coracoid transfer for collision athletes with or without glenoid defect due to potential high recurrence rate after arthroscopic soft tissue Bankart repair (ABR). In the meantime, Hill-Sacks remplissage (HSR) has been gaining popularity as an effective arthroscopic augmentation procedure. Since 2002, we performed rotator interval closure (RIC) as an augmentation in addition to ABR or arthroscopic bony Bankart repair (ABBR) for collision athletes and obtained satisfactory outcome. However, teen players demonstrated higher recurrence rate compared to twenties and thirties. Therefore, from 2012, we performed HSR as an additional augmentation for teen players besides ABR/ABBR and RIC. The purpose of this study was to assess the outcomes after arthroscopic stabilization in collision athletes who underwent shoulder stabilization under our treatment strategy. Methods: Between 2012 through 2015, 95 consecutive collision athletes underwent shoulder stabilization. Among those, only 2 patients (2%) underwent arthroscopic bony procedure for poor capsular integrity. Among the remaining 93 patients who underwent soft tissue stabilization, 65 were available for minimum 2 year follow-up (70%). Therefore, subjects consisted of 65 players including 54 rugby and 11 American football players (Table 1). There were 13 national top league, 24 collegeate, 21 junior or senior high school, and 7 recreational players. The mean age at surgery was 20 years (range, 16-36). The mean follow-up was 37 months (range, 24-64). We retrospectively reviewed intraoperative findings and surgical procedures using patient records including surgical reports and videos. We also investigated the mean time for sports return, functional outcome and recurrence rate. Pre- and postoperative Rowe scores were compared using paired t test. Results: Preoperative 3DCT of the glenoid demonstrated bony Bankart (fragment type) in 43 players (66%), attritional type in 16 (25%), and normal glenoid in 6 (9%). Mean glenoid bone loss was 15% (range, 0-25) and all of the glenoid with more than 10% bone loss retained bony fragment (Table 2). All 65 players demonstrated Bankart lesion and 15 had concomitant SLAP lesion (23%) which required repair. In addition, 5 players demonstrated capsule tear (8%), which were also repaired. Twenty four players (36%) underwent ABR or ABBR with RIC and forty one players (64%) underwent ABR or ABBR combined with HSR (Table 1).The mean time for sports return was 7 months (range, 4-13) after surgery. The mean Rowe score significantly improved after surgery from 65 (range, 55-75) to 92 (range, 65-100) (P < .001). Recurrence appeared in 2 cases (3%), both of which were junior or senior high school players who underwent ABR with HSR. Conclusion: Soft tissue stabilization combined with selective augmentation procedures for shoulder instability in collision athletes demonstrated satisfactory outcomes with low recurrence rate. Since the incidence of having bony Bankart lesion in collision athletes was very high, arthroscopic bony Bankart repair worked in many patients even with significant glenoid bone loss. Further, HSR seemed to be effective additional augmentation especially in young collision athletes. Table 1. Total ABR/ABBR with RIC ABR/ABBR with HSR Players 65 24 41 National top league 13 10 3 College league 24 8 16 Junior or senior high school 21 3 18 Recreational Level 7 3 4 Age at surgery (tears) 20(16-36) 23(15-36) 19(15-28) Mean Follow up(months) 37(24-64) 41(24-64) 35(24-60) Revision surgery 5 1 4 Table 2. Total(n=65) Glenoid morphology Fragment type 43(66%) Attritional type 16(25%) Normal glenoid 6(9%) Glenoid bone loss 15%(0-25)